Report of the Training Seminar on Use of Sampling in Population Census, 18-29 August 1980 (Office of the Registrar General, India, Ministry of Home Affairs, 1981)
Proceedings of the seminar, organized by the Office of the Registrar General and the Statistical Institute for Asia and the Pacific, Tokyo.